2007
DOI: 10.1111/j.1540-8167.2007.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of AV Delay Programming Methods for Hemodynamic Optimization during Cardiac Resynchronization Therapy

Abstract: An electrogram-based optimization method accurately predicts the optimal AVD among patients over a wide range of QRS intervals during CRT in both AS and AP modes. This simple technique may obviate the need for echocardiography for AVD programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 30 publications
3
91
1
2
Order By: Relevance
“…In this study, we also found that echocardiography-guided optimization of AV/VV delays was accurate and achievable, and this method was generally the first choice for postsurgery interval optimization in the several previously reported studies [13-15]. Optimal delays are determined by mitral inflow velocity profile and LV outflow tract velocity profile (VTI; reflecting the volume of blood ejected by the left ventricle to the aorta), which are obtained via Doppler echocardiography.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we also found that echocardiography-guided optimization of AV/VV delays was accurate and achievable, and this method was generally the first choice for postsurgery interval optimization in the several previously reported studies [13-15]. Optimal delays are determined by mitral inflow velocity profile and LV outflow tract velocity profile (VTI; reflecting the volume of blood ejected by the left ventricle to the aorta), which are obtained via Doppler echocardiography.…”
Section: Discussionsupporting
confidence: 53%
“…13,35,36 This method calculates sensed and paced AV delays that provide maximum hemodynamic response based on the measurement of electric conduction delays (ie, AV intervals and QRS duration). 19,20 The algorithm further accounts for LV lead location, which is generally considered an important variable in ensuring optimal patient response. 19,20 The results from the CRT-AVO study demonstrated that the SD algorithm recommended a customized AV delay that increased the acute hemodynamic responses in terms of percent change in LV dP/dtmax compared with fixed nominal AV delays of 100, 120, 140, or 160 milliseconds as well as the Ritter method and aortic velocity-time integral.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The algorithm further accounts for LV lead location, which is generally considered an important variable in ensuring optimal patient response. 19,20 The results from the CRT-AVO study demonstrated that the SD algorithm recommended a customized AV delay that increased the acute hemodynamic responses in terms of percent change in LV dP/dtmax compared with fixed nominal AV delays of 100, 120, 140, or 160 milliseconds as well as the Ritter method and aortic velocity-time integral. 19 Thus far, however, no large-scale clinical study has directly compared different methods of AV delay optimization to determine whether there are LV reverse remodeling benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doppler echocardiography may also be used to assess mitral inflow velocities (utilizing the Iterative or Ritter method, described below) as well as aortic and left ventricular outflow tract (LVOT) outflow velocities across several AV intervals to find the one that maximizes cardiac output. Invasive techniques involve direct endovascular intracardiac hemodynamic measurements (LV dP/dt or pulse pressure) [21][22][23][24][25][26][27][28][29][30]. The majority of the landmark CRT trials that utilized AV optimization employed either the Ritter [31,32] or Iterative [33] techniques.…”
Section: Effects Of the Atrioventricular Interval On Hemodynamicsmentioning
confidence: 99%